Scaphotrapeziotrapezoid fusion: long-term follow-up study - Minami, Akio; Kato, Hiroyuki; Suenaga, Naoki; Iwasaki, Norimasa (Journal of orthopaedic science : official journal of the Japanese Orthopaedic Association, 2003)
The long-term effectiveness of scaphotrapeziotrapezoid (STT) fusion is still controversial. We evaluated our clinical and radiological results of 30 STT fusions in 30 patients (average age 41 years; 23 males, 7 females). The follow-up period averaged 84 months. The indications were Kienböck’s disease (n = 23), isolated STT arthrosis (n = 6), and dislocation of the trapezium (n = 1). A total of 26 simultaneous associated procedures were performed. Excisional arthroplasty of the lunate was done in all 23 patients with Kienböck’s disease. Of the 30 total patients, 5 had postoperative pain ranging from mild to severe; 4 patients were dissatisfied with the results. Postoperative ranges of motion of the wrist were 84% of extension and 91% of flexion compared with preoperative motion. The postoperative grip strength improved to 27 kgf from the preoperative value of 18 kgf. Altogether, 26 patients returned to their previous activities. All patients obtained uneventful STT fusion in an average of 11.2 weeks. Eight patients (27%) experienced postoperative complications; seven had radioscaphoid arthroses, five had trapeziometacarpal arthrodeses, and one had a flexor pollicis longus tendon rupture. Although radioscaphoid arthrosis occurred in 23% of this series after STT fusion, the results suggest that it is an effective procedure for Kienböck’s disease and isolated STT arthrosis.